The Letters of Heloise and Abelard : A Translation of Their Collected Correspondence and Related Writings - McLaughlin, Mary Martin; Wheeler, Bonnie; Translated and edited by McLaughlin, Mary Martin; Wheeler, Bonnie (New York, NY Palgrave Macmillan, 2009)
The letters of Heloise and Abelard will remain one of the great, romantic and intellectual documents of human civilization while they, themselves, are probably second only to Romeo and Juliet in the fame accrued by tragic lovers. Here for the first time in Mart Martin McLaughlin's edition is the complete correspendence with commentary.
Include Appendices, Notes and Bibliography.
A Translation of Their Collected Correspondence and Related Writings.
Keywords: Theologians -- Abbesses, Christian -- France -- Heloise